Van der Waals epitaxial growth and optoelectronics of a vertical MoS2/WSe2 p–n junction - Yu Xiao; Junyu Qu; Ziyu Luo; Ying Chen; Xin Yang; Danliang Zhang; Honglai Li; Biyuan Zheng; Jiali Yi; Rong Wu; Wenxia You; Bo Liu; et al. (Frontiers of Optoelectronics, 2022)
Abstract Two-dimensional (2D) transition metal dichalcogenides (TMDs) have attracted extensive attention due to their unique electronic and optical properties. In particular, TMDs can be flexibly combined to form diverse vertical van der Waals (vdWs) heterostructures without the limitation of lattice matching, which creates vast opportunities for fundamental investigation of novel optoelectronic applications. Here, we report an atomically thin vertical p–n junction WSe2/MoS2 produced by a chemical vapor deposition method. Transmission electron microscopy and steady-state photoluminescence experiments reveal its high quality and excellent optical properties. Back gate field effect transistor (FET) constructed using this p–n junction exhibits bipolar behaviors and a mobility of 9 cm2/(V·s). In addition, the photodetector based on MoS2/WSe2 heterostructures displays outstanding optoelectronic properties (R = 8 A/W, D* = 2.93 × 1011 Jones, on/off ratio of 104), which benefited from the built-in electric field across the interface. The direct growth of TMDs p–n vertical heterostructures may offer a novel platform for future optoelectronic applications. Graphical Abstract